Paranoplocephala nearctica Haukisalmi & Henttonen, 2007, n. sp. - Haukisalmi, Voitto; Henttonen, Heikki (Zenodo, 2007)
Paranoplocephala nearctica n. sp. (Figs. 3–4) Type host: Myodes rutilus , Myomorpha, the northern red-backed vole. Type locality: unnamed lake near North Fork of Koyukuk River, Gates of the Arctic National Park and Preserve (GAAR), northern Alaska, U.S.A., 67o27'11.2"N, 150o51'00.2"W. Site: Small intestine (duodenum or jejunum). Deposited specimens: Holotype: MSB Endo 1 (field code AF 61624), from My. rutilus (UAM 78325) collected on 23rd July 2002 at an unnamed lake near North Fork of Koyukuk River, Gates of the Arctic National Park and Preserve (GAAR), northern Alaska, U.S.A. (67o27'11.2"N, 150o51'00.2"W). Collectors: H. Henttonen, K. Hildebrandt, J. Laakkonen and J. Niemimaa. Paratype: MSB Endo 2 (field code AF 59966), from My. rutilus (UAM 79092), collected on 14th July 2002 at Agiak Lake, GAAR, Alaska (68o95'01.4"N, 152o57'36.2"W). Collectors as for the holotype. Voucher specimens: i) MSB Endo 4 (AF 59962), from My. rutilus (UAM 79088), Agiak Lake, GAAR, Alaska, ii) MSB Endo 7 (AF 61179), from My. rutilus (UAM 78871), Agiak Lake, GAAR, Alaska, iii) MSB Endo 11 (NK 124538), from My. rutilus , Dot Lake, Highway 2, eastern Alaska, iv) MSB Endo 12 (NK 124627), from My. rutilus , Dawson City, Yukon, Canada, v) MSB Endo 10 (IF 6991), from My. rutilus , Stikine River, British Columbia, Canada, vi) MSB Endo 8 (IF 6889), from My. gapperi , Stikine River, British Columbia, vii) MSB Endo 9 (IF 6941), from My. gapperi , Stikine River, British Columbia, viii) MSB Endo 3 (AF 49312), from Mi. longicaudus (UAM 58405), Mt. Kathryn, Yukon-Charlie Rivers National Preserve, Alaska. Description: Based on eleven specimens from My. rutilus from various localities in Alaska, northwestern British Columbia and western Yukon (Tables 1 and 2). Fully gravid strobila 65–104 (n=4) long; maximum width (0.75–1.50, 1.13, n=9) attained in pregravid or gravid proglottids. Number of proglottids ca. 300 (n=1). Proglottids craspedote, but velum short in wellrelaxed specimens. Length/width ratio of mature proglottids 0.25–0.57 (0.41, n=21), of ...